2015
DOI: 10.3390/ijms161125957
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics: A New Way to Illustrate the Crosstalk between Infectious Diseases and Host Microbiome

Abstract: Microbes have co-evolved with human beings for millions of years. They play a very important role in maintaining the health of the host. With the advancement in next generation sequencing technology, the microbiome profiling in the host can be obtained under different circumstances. This review focuses on the current knowledge of the alteration of complex microbial communities upon the infection of different pathogens, such as human immunodeficiency virus, hepatitis B virus, influenza virus, and Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 126 publications
0
34
0
Order By: Relevance
“…[24][25][26][27][28][29] HBV has been found to alter the normal gut microbiota. 30,31 Moreover, the composition and diversity of enteric fungi were also found to be positively correlated with disease progression in patients with different degrees of chronic HBV infection. 32 Maternal microbiota have been found to affect various health conditions of offspring, such as the fetal microbiome 33 and fetal metabolism of lipid and glucose.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[24][25][26][27][28][29] HBV has been found to alter the normal gut microbiota. 30,31 Moreover, the composition and diversity of enteric fungi were also found to be positively correlated with disease progression in patients with different degrees of chronic HBV infection. 32 Maternal microbiota have been found to affect various health conditions of offspring, such as the fetal microbiome 33 and fetal metabolism of lipid and glucose.…”
Section: Discussionmentioning
confidence: 95%
“…HBV has been found to alter the normal gut microbiota . Moreover, the composition and diversity of enteric fungi were also found to be positively correlated with disease progression in patients with different degrees of chronic HBV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also linked the microbiota composition with modification in epigenetic patterns in newborns, increasing the need to further investigate the role of the microbiota in the understanding of the phenotypic plasticity in teleosts (Bhat & Kapila, ; Cortese, Lu, Yu, Ruden, & Claud, ; Indrio et al., ; Rossi, Amaretti, & Raimondi, ). Because host–microbiota interactions are narrowly related to the host physiology (Donaldson et al., ; Klaasen et al., ; Liu et al., ; Scanlan et al., ; Wu & Lewis, ; Zhang, Lun, & Tsui, ), it is suspected that bacterial composition of microbial communities will tightly adapt to artificial rearing conditions (water composition, food, environmental bacterial community), which in turn will affect the ability of hatchery‐reared parrs to adapt to natural conditions once released.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported in several studies, that the microbiota in the sputum sample of pulmonary tuberculosis patients are more diverse than those of healthy participants [28]. Previous studies have already reported many genera that were unique to in the sputum of pulmonary tuberculosis patients, they are Phenylobacterium, Stenotrophomonas, Cupriavidus, Caulobacter, Pseudomonas,Thermus, Sphingomonas ,Pelomonas, Acidovorax, Brevibacillus, Methylobacterium, Diaphorobacter, Comamonas, Mobilicoccus, Fervidicoccus, Serpens, Lactobacillus, Thermobacillus, Auritidibacter, Deinococcus, Lapillicoccus, Devriesea respectively [29]. But, when we performed our analysis only with indian sample, we have identified a wide range of genera.…”
Section: Figure4 Aphylogenetic Tree For North India Sample B Phylmentioning
confidence: 99%